THE USE OF SONG MEDIA TO IMPROVE VOCABULARIES ACHIEVEMENT OF SEVENTH GRADE STUDENTS IN SMP GAJAH MADA MEDAN - Yusnani Timotea Samosir; Fenty Debora Napitupulu; Sahat Taruli Siahaan (Jurnal Scientia, 2023)
The purpose of this research was to understand how song media can improve the vocabulary development of 7th grade students of SMP Gajah Mada Medan. The subjects of this study were 7th grade students of Gajah Mada Middle School, Medan. There are two types of data collected during research, quantitative and qualitative data. The instruments for collecting quantitative data are vocabulary tests, while questionnaires and observation sheets are for qualitative data. Based on qualitative data, students were active and enthusiastic in participating in the teaching and learning process. Quantitative data shows that students' ability to master vocabulary increased from pre- test to post-test in cycle I and cycle II. This can be seen from the average student score and the percentage of students who scored ≥ 75. The average student score and the percentage of students who obtained a pre-test score ≥ 75 was 63.95 and in cycle I was 72.23 and for cycle II it was 83,19. From these results, it can be seen that there has been an improvement, meaning that students have understood the treatment and are starting to actively master vocabulary. In the third test, the lowest score was 30 and the highest score was 100. It can be said that the last test was a good improvement because many students got high scores in the third test and they were more active and had good motivation in mastering vocabulary than before. The qualitative data found that students were enthusiastic about learning vocabulary by using songs as media. This can be seen from the student observation sheet. The author keeps observation sheets in cycle 1 and cycle II. In cycle I, students were less serious in learning, but in cycle II students were serious, active and enthusiastic in learning. The results show that there is an increase in students' ability to master vocabulary by using song media. The use of song media helps students learn vocabulary more easily.